2020
DOI: 10.4103/nmj.nmj_124_19
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of socio-demographic variables and attitude to condom use in HIV/AIDS prevention among students in some selected Nigerian Universities

Abstract: Background: Unprotected heterosexual sexual act has been correlated with unwanted pregnancy and sexually transmitted diseases (STDs) especially HIV/AIDS, which still has a high endemicity in Africa. This study aimed to determine the association between socio-demographic variables (SDVs), sexual experience, and the use of condom. Setting and Design: This was a cross-sectional study comprising 542 undergraduate students, randomly selected from three Nigerian universities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…However, 29.7% of the respondents did not know that condom use does not totally prevent STD infection. This lack of knowledge has also been reported in a cross-sectional study comprising 542 undergraduate students, randomly selected from three Nigerian Universities [28]. The most common reasons given for the use of condoms were prevention of pregnancy (91.7%) and the ability to provide protection from STDs (89.1%) [28].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, 29.7% of the respondents did not know that condom use does not totally prevent STD infection. This lack of knowledge has also been reported in a cross-sectional study comprising 542 undergraduate students, randomly selected from three Nigerian Universities [28]. The most common reasons given for the use of condoms were prevention of pregnancy (91.7%) and the ability to provide protection from STDs (89.1%) [28].…”
Section: Discussionmentioning
confidence: 74%
“…This lack of knowledge has also been reported in a cross-sectional study comprising 542 undergraduate students, randomly selected from three Nigerian Universities [28]. The most common reasons given for the use of condoms were prevention of pregnancy (91.7%) and the ability to provide protection from STDs (89.1%) [28]. This suggested that these young adults were not aware that condom use does not prevent STDs [27].…”
Section: Discussionmentioning
confidence: 76%